An approach for dynamically load balanced flow scheduling(DLBS) in cloud - A. Sheela, Mrs.; J. Ranjani, Mrs. (International Journal of Engineering and Technology, 2018)
The Paper based on load balanced flow scheduling algorithm. This algorithm is used in which huge amount of data send to multiple servers frequently without a few traffic, isolation in open flow network. In existing load balanced algorithm based on huge amount of data send to several server but it suffers from that that algorithm is not support to other open flow networks model and transmission pattern. In this proposed load balanced scheduled algorithm with Round Robin deals with maximizing the network throughput dynamically. The (Dynamically Load Balanced Flow Scheduling) DLBS problem is formulated , considerably a efficient heuristic scheduling algorithms was developed for the two typical Open Flow network model, they have data flow from time slot. The outcome represents load-balanced scheduling algorithms Round Robin and LOBUS with effective improvement in DLBS move toward will carry to the data centers. Plenty of researchers pay large number of attention on software-deﬁned networking.